Shift work and the risk of diabetes mellitus among Japanese male factory workers - Morikawa, Yuko; Nakagawa, Hideaki; Miura, Katsuyuki; Soyama, Yoshiyuki; Ishizaki, Masao; Kido, Teruhiko; Naruse, Yuchi; Suwazono, Yasushi; Nogawa, Koji (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'This study investigated whether shift work is a risk factor for the development of diabetes mellitus. ' ' METHODS ': 'The workers, 2860 men in a sash and zipper factory in the Toyama prefecture of Japan, were followed for 8 years, and the incidence rate of diabetes mellitus was determined. The cohort contained fixed daytime blue-collar workers, shift blue-collar workers, and white-collar workers. The workers were considered to have diabetes mellitus if, in their annual health examination, they had a glycated hemoglobin level of ≥6.1 or if the diagnosis had been made by a hospital physician. The relative risks were estimated by Cox’s proportional hazards regression model. ' ' RESULTS ': 'Among the 2860 workers, there were 87 cases of new-onset diabetes mellitus, resulting in an incidence rate of 4.41 per 1000 person-years. The age-adjusted incidence was highest for the two-shift workers and lowest for the white-collar workers. The relative risk of diabetes mellitus for the two-shift workers and the three-shift workers compared with the fixed daytime workers was 1.73 and 1.33, respectively, after adjustment for all the confounding factors, but these values were not statistically significant. When the white-collar workers were used as a reference group, a significantly increased risk of diabetes mellitus was found for the two-shift workers (relative risk was 2.01 after adjustment for all confounding factors), but not for the three-shift workers or the fixed daytime blue-collar workers. ' ' CONCLUSIONS ': 'The study suggests that shift work is a risk factor for the onset of diabetes mellitus and that there is a different risk associated with different shift schedules.
Keywords: cohort study; diabetes mellitus; factory worker; glucose tolerance; glycated hemoglobin; Japan; man; shift work